The influence of socialization on employees' assimilation tactics in Malaysian MNC organizations / Kardina Kamaruddin ... [et al.] - Kamaruddin, Kardina; Ali, Noor Malinjasari; Azizan, Nurul Nadzirah (Universiti Teknologi MARA, Kedah, 2021)
Globalization increases the opportunities of foreign companies to enter new markets. Adequate assimilation programs are often not available to foreigners and local workers to completely understand and adapt to the new organizational culture presented to them. Socialization tactics represent a technique for addressing access to cultural assimilation in multi-national companies (MNC) within the host countries. This study is to examine the influence of socializatio n tactics on employees' assimilation in MNC organizations (n=396). Data were collected from a few private MNC organizations in the northern region of Malaysia. The independent variable in the study is mainly known as socialization tactics which can be divi ded into two; institutionalized tactics and individualized tactics. We examined the extent of employees' assimilation effectiveness, the link between socialization tactics and employees' assimilation, the influence of institutionalized and individualized tactics on employees' assimilation, and to determine the relationship between institutionalized and individualized tactics and also the dimension of employees' assimilation (familiarity with coworkers, familiarit y supervisor, acculturation, recogniti with on, involvement, job competency and role negotiation). Among the independent variables, institutionalized tactics were found to be the dominant factor in influencing employees' assimilation among employees in MNC organizations. These findings support the f easibility to comprehend the socialization approach as a key to the effectiveness of employees' assimilation process. This paper will benefit the MNC organizations to compete well and drive towards its sustainable growth within the industry.